TINGKAT KEPUASAN MAHASISWA TERHADAP LAYANAN AKADEMIK - Hamdani Hamdani; Asep Nursangaji (Jurnal AlphaEuclidEdu, 2020)
Nowadays, there are several LPTK in West Kalimantan that have mathematics education courses apart from FKIP UNTAN. This is a challenge for FKIP UNTAN to become the main choice for prospective students. So, it is very important for the FKIP UNTAN mathematics education department to provide quality academic services to students so that they feel satisfied. One of the student satisfaction assessments index in academic services in the Mathematics Education Department of FKIP UNTAN is academic guidance and course implementation. This study will examine how high the level of student satisfaction with academic services in the Mathematics education Department FKIP UNTAN . Furthermore, it will be known what service items should be improved and developed in an effort to increase student satisfaction. The method used is descriptive method with a survey form involving students in 3rd, 5th, and 7th semester. The instrument used is a satisfaction questionnaire. The level of student satisfaction with academic guidance services is 2% of students are not satisfied, 6% of students are not satisfied, 30% of students are satisfied, 32% of students are quite satisfied, and 30% of students are very satisfied. Then for the level of student satisfaction with the lecture process as much as 2% of students were not satisfied, 5% of students were not satisfied, 27% of students were satisfied, 36% of students were quite satisfied, and 30% of students were very satisfied.Keywords: Satisfaction; Academic Services; Academic Guidance; The Lecture Process.